2022
DOI: 10.3390/nu14030567
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Vitamin D Deficiency Status in Malaysia

Abstract: Vitamin D is essential for maintaining serum calcium levels, ensuring sufficient bone mineralization, immunomodulatory properties, and a protective effect on the cardiovascular system, renal disease, cancer, as well as in pregnancy. Vitamin D deficiency is prevalent worldwide, and it is not related to a country’s development index. However, the data on vitamin D deficiencies are primarily taken from out-of-date, small-scale studies on target age groups or specific diseases, rather than from large-scale, popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
1
11
0
1
Order By: Relevance
“…Sun exposure enables vitamin D synthesis, with approximately 50% to 90% absorbed through the skin [ 1 ]. This process involves multiple steps, beginning with 7-dehydrocholesterol in the skin and through exposure to ultraviolet B rays [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun exposure enables vitamin D synthesis, with approximately 50% to 90% absorbed through the skin [ 1 ]. This process involves multiple steps, beginning with 7-dehydrocholesterol in the skin and through exposure to ultraviolet B rays [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its equatorial position, Malaysia experiences a relatively consistent number of daylight hours year-round. Surprisingly, despite Malaysia’s equatorial location with abundant sunlight, local studies have revealed a significant prevalence of vitamin D deficiency among Malaysians [ 2 , 13 ]. This discrepancy is noteworthy given the country’s tropical climate, which receives an ample 7–8 h of intense daily sunlight, far exceeding the 6–8 min required for adequate vitamin D production, as stated in a previous Nordic study [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D, generally known as calciferol, is a fat-soluble vitamin [ 9 ]. There are two main forms of vitamin D: ergocalciferol (vitamin D 2 ) and calciferol (vitamin D 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is mostly synthesised endogenously when the skin is exposed to ultraviolet B from sunlight, which produces cholecalciferol, and subsequently transported to the liver by the vitamin D binding protein (VDBP). The first hydroxylation occurs in the liver, where 25-hydroxyvitamin is converted to 25-hydroxyvitamin D 3, which is the inactive form of vitamin D, with the help of 25 hydroxylase enzymes [ 9 , 15 ]. Subsequently, the vitamin D-binding protein binds to 25-hydroxyvitamin D 3 and transports it to the kidney for a second hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation